Surgical Outcome of Decompressive Craniectomy in Traumatic Brain Injury: A study in a Tertiary Care Hospital of Bangladesh (KYAMC Journal, 2022)
Background: Traumatic Head injury is one of the most important causes of death. Decompressive craniectomy is said to be the best way to reduce otherwise intractable intracranial pressure and its complications in traumatic brain injury (TBI). But we have not enough information regarding the outcomes and effectiveness of decompressive craniectomy in TBI.Objectives: The aim was to assess the outcomes and effectiveness of decompressive craniectomy in TBI.Materials and Methods: Prospective observational study which conducted in Khwaja Yunus Ali Medical College and Hospital, Sirajganj and TMSS Medical College & Hospital, Bogura, Bangladesh in collaboration with the Department of Neurosurgery, from July 2018 to December 2021. Total 32 patients with severe TBI diagnosed and treated in those hospitals who recruited as the samples and outcomes of the patients evaluated through Glasgow Coma Scale (on which scores range from 3 to 15, lower scores indicating reduced levels of consciousness). All patient data were collected, processed, analyzed then disseminated by using MS Office 2019 and SPSS version 23 programs.Results: Analyzing hospital staying we observed, the mean (±SD) days of mechanical ventilation, days of ICU staying, days of hospitalization were 8.88 ± 2.54, 10.21 ± 3.16 and 15.57 ± 4.51 days respectively. Finally, the mean (±SD) Extended Glasgow Outcome Scale score of all the patients was found as 9.1. and unfavorable Extended Glasgow Outcome Scale score (1 to 4) was found in 56% patients. In this study, finally death cases were 22%.Conclusion: Decompressive craniectomy ensures better outcome for survival but the limitation is quality of life issues after survival especially among poor GCS (3-6) group. Prompt hospitalization, early diagnosis, proper ICU and ventilation facilities can ensure more satisfactory outcomes in TBI. KYAMC Journal Vol. 13, No. 03, October 2022: 153-157